Hoffa fracture associated with tibial shaft fracture and multiple ligament avulsion fractures: A case report. (April 2020) - Liu, Qian; Wang, Wanchun; Fan, Wei; Zhu, Weihong
Abstract: Hoffa fracture combined with tibial shaft fracture and multiple ligament avulsion injuries is extremely rare. Herein, we report a case of medial Hoffa fracture with associated fracture of tibial shaft and avulsion fractures of multiple ligaments secondary to knee dislocation. A 17-year-old female with history of a motorcycle accident was referred to our hospital after knee joint reduction at a regional trauma center. Preoperative radiology revealed a medial Hoffa fracture associated with tibial shaft fracture, inferior pole patellar fracture, fibular head fracture and multiple ligament avulsion fractures including anterior cruciate ligament, posterior cruciate ligament and medial collateral ligament. A less invasive approach via arthroscopy-assisted technique and minimally invasive plate osteosynthesis (MIPO) technique was used for fracture reduction and fixation. Six months postoperatively, the patient had arthrofibrosis and adhesiolysis under arthroscopy was performed. At the last follow-up of 24 months, the patient regained knee full range of motion and returned to pre-injury level of activities. Although minimally invasive techniques were used to speed recovery, the orthopaedic surgeon should still be aware of the possibility of postoperative arthrofibrosis as multiple site fractures may need longer immobilization.